The Impact of Compensation and Career Development on Employee Retention in Educational Institutions : A Case Study At PT XYZ - Puspita, Mugi (CV ODIS, 2025)
Employee retention is a crucial factor in maintaining organizational stability and competitiveness. This study aims to analyze the influence of compensation and career development on employee retention at PT Rumah Belajar Indonesia. The research employs a quantitative approach using survey data collected from employees. Data analysis is conducted using multiple regression to determine the extent of the impact of compensation and career development on retention. The findings indicate that both compensation and career development have a significant positive effect on employee retention. Competitive compensation packages and well-structured career development programs enhance job satisfaction and organizational commitment, leading to lower turnover rates. These results highlight the importance of implementing effective HR strategies to improve employee retention. The study provides valuable insights for HR practitioners in designing policies that foster long-term employee engagement and organizational sustainability.